MATRIK TRANSFORMASI PADA RUANG BARISAN ORLICZ - Haryadi Haryadi (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2022)
In this study will be characterized a matrix that maps the space of the Orlicz sequence space to the space of the bounded sequence and the convergence sequence. This study is carried out by generalized the matrix mapping on lp space, 1<=p<∞, to the Orlicz sequence space. This results establishes a necessary and sufficient conditions for a matrix that maps the Orlicz sequence space to the bounded sequence space, convergence to sequence space and the convergence sequence space.